The chert workshop of Tozal de la Mesa (Alins del Monte, Huesca, Spain) and its exploitation in historical times (Journal of Lithic Studies, 2016)
In 2012, during a field survey to locate primary outcrops of cherts in the Carrodilla Mountain Range (Huesca, Spain), abundant remains of chert-knapping were found next to nodular cherts in primary and sub-primary position from the Garumnian limestones. Chert knapping evidences were discovered in Tozal de la Mesa mount, near the town of Alins del Monte (Huesca, Spain), in the first prepyrenean foothills of the province of Huesca.In order to define the features of the workshop and to determine their limits, in 2015 we conducted a field survey. Due to these works, it has been possible to define the perimeter of the chert workshop as well as to collect abundant lithic remains of chert and other rocks (e.g., ophites) that may have been directly related to chert exploitation.In this paper we are going to present the results obtained after the textural, micropaleontological, petrographic and mineralogical characterization of these cherts as well as the results of the techno-typological and traceological analyses. Moreover, we will define the features of the chert workshop and its functionality.The first approach to contextualize the recovered materials of Tozal de la Mesa workshop area has allowed determining an exploitation of the Garumnian cherts that has lasted until the late nineteenth century according to some recovered products (e.g., pottery) and to oral sources.